2023
DOI: 10.1108/k-03-2022-0319
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the complementary effects of multiple strategic orientations on firm performance: an interplay of entrepreneurial, sustainability and market orientation

Abstract: PurposeThis study aims to investigate how the interplay of multiple strategic orientations influences the growth-based performance of small and medium enterprises (SMEs). The authors have specifically examined the direct and complementary effects of multiple strategic orientations [i.e. entrepreneurial orientation (EO), market orientation (MO) and sustainability orientation (SO)] on firm performance.Design/methodology/approachThe data have been collected from 410 SMEs operating in Pakistan.FindingsThe results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…Several studies have examined the role of sustainability-oriented corporate strategies in business performance (e.g. (Adomako et al, 2019;Khizar et al, 2023;Ruiz-Ortega et al, 2021),). Chistov et al (2023) studied the role of sustainability strategies in firm growth and found the importance of timing in the entrepreneurial process, demonstrating that including sustainability goals at a later, more established stage of the process offers much greater growth potential.…”
Section: Review Of Literature and Conceptual Developmentmentioning
confidence: 99%
“…Several studies have examined the role of sustainability-oriented corporate strategies in business performance (e.g. (Adomako et al, 2019;Khizar et al, 2023;Ruiz-Ortega et al, 2021),). Chistov et al (2023) studied the role of sustainability strategies in firm growth and found the importance of timing in the entrepreneurial process, demonstrating that including sustainability goals at a later, more established stage of the process offers much greater growth potential.…”
Section: Review Of Literature and Conceptual Developmentmentioning
confidence: 99%
“…The review of the SO literature highlighted that organizations have proactively started to develop and deploy SO, not only due to the increasing pressures from stakeholders and the call for sustainable development but also because of the potential positive organizational outcomes of managing SO (e.g. Aboelmaged and Hashem, 2019;Jin et al, 2019;Muhammad Auwal et al, 2020;Khizar and Iqbal, 2020). To this end, sustainability-oriented firms reflect their inclination to behave in a socially and environmentally responsible manner to comply with the demands of stakeholders to achieve superior financial and nonfinancial performance benefits over their counterparts in the industry.…”
Section: Introductionmentioning
confidence: 99%